Efficiency of ITS1-5.8S-ITS2 region in identifying Cordyceps species - Thu Hien, Le Thi; Hong Hanh, Ha (Vietnam Journal of Biotechnology, 2020)
Cordyceps genus is a well-known traditional medicine worldwide. It contains abundant physiological active compounds that were demonstrated to perform benefit in reducing progression of cancer as well as protecting human health. Accurately classifying species in this genus is essential in order to prevent commercial counterfeit medicines. Nowadays, a taxonomic classification of species based on DNA sequences can overcome the existed limitation in identifying by using only morphological characteristics of this genus. DNA barcodes are standard short genomic regions that are universally present in target lineages and has sufficient sequence variation to discriminate species in the genus. A variety of loci has been suggested as DNA barcodes for plants, including genes and non-coding regions in the nuclear and plastid genomes such as psbA-trnH, matK, rbcL, and ITS. Thus, the objective of this study was to identify selected species of Cordyceps genus using DNA barcodes. Seven strains of Cordyceps were collected. Total DNA extraction and purification, PCR amplification and DNA sequencing were performed with standard chemicals and kits. The candidate ITS1-5.8S-ITS2 region was amplified and sequenced. Data were analyzed using Bioedit 7.2.6 and MEGA 7 softwares. Analysis of seven obtained DNA barcode sequences of collected samples revealed that the ITS1-5.8S-ITS2 region provided high species discriminating power for Cordyceps genus. Accordingly, phylogenetic trees based on this DNA barcode exhibited six samples had closed relationship to Cordyceps militaris, while another specimen was the nearest neighbor to Cordyceps sinensis with average similarities at 99.82% and 99.81%, respectively. Our results support the identification of valuable medicinal plant species within Cordyceps genus.